49. ĐÁNH GIÁ KẾT QUẢ PHẪU THUẬT GÃY KÍN CỔ PHẪU THUẬT XƯƠNG CÁNH TAY BẰNG NẸP VÍT KHÓA TRÊN BỆNH NHÂN LỚN TUỔI TẠI BỆNH VIỆN THỐNG NHẤT (Tạp chí Y học Cộng đồng, 2024)
Objectives: To describe the clinical characteristics, X-ray images and results of treatment of proximal humerus fractures by the method of combining the locking plate at Thống Nhất Hospital. Subjects and Methods: Retrospective and prospective cross-sectional descriptive study on 19 patients between 2021 and 2024. Result: Mean age of study patients is 70,5. The results of post-surgery correction without displacement accounted for a high rate with 94,7%. The humerus neck angle after surgery achieved good results, accounting for 100%. The rate of patients without pain after surgery accounted for 81.3%. The percentage of patients with good overall results accounted for 63,3%.
Keywords: Gãy cổ phẫu thuật xương cánh tay; nẹp vít khóa; kết hợp xương